Pendidikan Islam Masa Periode Safawiyah dan Mughal - Noor Arofatun Muthoharoh (La-Tahzan: Jurnal Pendidikan Islam, 2022)
The Middle Period in the Periodization of Islamic History refers to the existence of three major kingdoms namely the Ottoman Empire in Turkey, the Safavid Empire in Persia and the Mughal Empire in India. These three kingdoms in the middle period illustrate the shift of non-Arab domination after the Arab domination in the classical period. In general, the medieval period is considered a period of decline. However, the historical facts about education during the three kingdoms provide a picture of development and progress. During the Ottoman Turkish period, madrasas were encouraged to study various sciences. Many educational institutions emerged during the reign of the Ottoman Empire, one of which was the madrasa. The first Ottoman madrasah was founded in Izmir in 1331 AD. The state of education in the Safawi Kingdom was shown by the existence of a very thick academic atmosphere. Among them is shown by the existence of tolerance and freedom of opinion. Despite the harsh indoctrination during the period of Shah Abbas II, the freedom of liberal thought had gained momentum. In the Mughal Empire, education received considerable attention. The Kingdom encourages mosques as a place of religious learning for the community in addition to being a place of worship. The mosques have been provided with ulama who will teach various branches of religious knowledge. In fact, the mosque has also provided special rooms for students who want to live in the mosque during their education.